(untitled) (CIPEEX, 2025)
Introduction: Cyclophosphamide (CFM) is an alkylating agent of the oxazaphosphorine class, widely used in the treatment of multiple pathologies, including systemic lupus erythematosus (SLE), which is a chronic, autoimmune, inflammatory, systemic disease with no cure. Objective: To compare the efficacy of cyclophosphamide in the main manifestations of systemic lupus erythematosus (SLE). Method: This is a systematic review of the literature, in which data were collected from a bibliographic search of databases. The inclusion criteria for articles were the use of the descriptors "Systemic Lupus Erythematosus" AND "Cyclophosphamide" AND "Efficacy" AND "Contraindications," as well as articles in English or Portuguese from studies published between 2000 and 2024. Results: When analyzing the efficacy of CFM in SLE presentations, we noted that in patients with proliferative glomerulonephritis (PNG), the superiority of cyclophosphamide use is evident when compared to the isolated use of corticosteroids (CS), as well as in the treatment of lupus nephritis (LN), where the addition of cyclophosphamide to corticosteroid therapy improved the renal condition of patients and reduced the risk of renal failure. In addition to its use in renal manifestations, CFM can be used in the treatment of neuropsychiatric, cardiovascular, and pulmonary manifestations. Conclusions: CFM as a choice with level A recommendation and evidence for proliferative nephritis; level B in myelopathy and membranous nephritis; level C in acute pneumonitis, pulmonary hemorrhage, interstitial lung disease, and pulmonary hypertension; and level D in refractory pericarditis.